(3TQM GdBLQhejIs - (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO , J (B905 (3g` s; (3GHf BoLoqQhe, eMeO Hf eMeO Hf OGhO GdUfgGLj, CHh YHO Gddg,J (B723 (3g` s ((3QMGd GdLdLhdj s)
(3ChdgG (B:s
(3hHYO, agPG TQM dCdaGX GdBLQhejI aj kChd GdYQHjI jfJaY Hg GdeHJOF hdG jMJGL Edjg GdefJgi s
(3BNQgG (B:s
(3hRGO GHf eGdc (B-(3JHYkG dWGFaI(B- (3bSekG KGdKkG heG CTHg Pdc ef CeKdI GdbSejf GdChdjf Ch GdKdGKI hgPg BNQ eG CQOfG PcQg Ydi gPg GdebOeI s
(3Vef eLehY s
(3GdJYbjHIs
(3YdjgG HYV GdTQhM hGdahGFO hcJH GdeJf HGdMeQIs
(3GdfSNI HgG MhGTs
(3fSNI ajgG VHWs
(3cJHgG QMGd GdLdLhdi HChdgG JedcGf ChdgeG YGe (B1253(3g`s
(3hGdBNQ YGe (B1266(3g`s
Keywords: (3GdfMhs